Medical cannabis - Silvia Kochen (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Health is a human right. In order to guarantee that right, it is fundamental that all activities concerning health in different contexts (clinical, research, teaching) contribute to the construction of an efficient system that promotes excellence, equity, justice, and solidarity. In this issue, we take on alternatives regarding the use of medical cannabis from this perspective. Health research and its contribution to knowledge - in particular with respect to the development of new pharmaceuticals - represents not only a challenge related to technology and production, but also an opportunity for ensuring the autonomy of the health system.